Ruth’s Superiority Complex as Seen in Kazuo Ishiguro’s Never Let Me Go - Maya Bella; Emilia Tetty Harjani (Conscientia, 2020)
This study is about Ruth’s superiority complex as seen in Kazuo Ishiguro’s Never Let Me Go. The objectives of this study were to find out the characteristics of Ruth’s superiority complex and the effects of superiority complex toward Ruth’s behavior. In conducting the research, the writer used qualitative research using the psychoanalysis approach which was based on Adler’s psychoanalytic theory and library research to collect the data. The result of the discussion revealed that Ruth showed excuses, aggression, and withdrawal. In aggression, Ruth demonstrated depreciation and accusation, while in withdrawal, Ruth showed moving backward and hesitation. The effects of Ruth's superiority complex toward her behavior are that she created an unrealistic goal, and she lived in dogmatic life and narrow perspective.